A case based learning model in therapeutics - Jesus, Ângelo (2012)
Nowadays, learning a Pharmaceutical Profession is an increasing challenge. Apart from traditional texts, lectures and self-guided individual learning, pharmaceutical educators are encouraged to find and implement ways to promote higher order thinking, collaborative learning and to increase students’ motivation. One way of achieving these objectives is to complement traditional learning methods with the development and implementation of Case Based Learning (CBL), supported in real life situations.Methods regarding real problems stand in contrast to a more traditional approach to learning and instruction. They promote learner-centered, small group, interactive learning experiences, instead of large group, didactic, teacher-centered instruction. Developing such a learning approach can be a challenge. In this sense, it becomes relevant to promote and share experiences already underway and by doing so, disseminate knowledge in this field. It is our goal with this text toshare our experience in the design and implementation of a Case Based Approach to Therapeutics.